A flexible and time-efficient schedule-based communication tool for integrated lighting and thermal simulations of spaces with controlled artificial lighting and complex fenestration systems. Issue 4 (3rd July 2016) - Vera, Sergio; Bustamante, Waldo; Molina, Germán; Uribe, Daniel
Abstract : Complex Fenestration Systems (CFS) incorporate a non-specular layer within the window assembly (e.g. undulated and perforated screens). CFS are often incorporated to the building façade for improving building thermal and visual performance. Thermal–lighting simulations of spaces with CFS are carried out with different tools. However, an integrated lighting and thermal analysis is a complex task to be implemented at the design stage of buildings that incorporates CFS. This paper presents mkSchedule, a new Radiance-based tool that allows the flexible and time-efficient generation of a schedule for the CFS position and luminaries power fraction. The methodology incorporates the three-phase method and use scripts written in Lua programming language. The schedule can be used for detailed thermal–lighting simulations. This work presents the application of this methodology to an office space, showing that the methodology is flexible enough to set different CFS and luminaries' controls, providing annual schedule in short computing time.